2020
DOI: 10.35808/ijeba/431
|View full text |Cite
|
Sign up to set email alerts
|

Use of Information Technology to Increase Economic Efficiency and Credibility in Public Administration in the Context of Digitization

Abstract: Purpose: The article analyzes the use of information technologies to increase the level of economic efficiency and trust in public administration in Ukraine. Design/Methodology/Approach: We use the concept of digital management for the purpose of integrated interaction of municipal and state structures with business, civil society institutions and the population. Findings: The conducted research concludes the active digital transformation of public administration in Ukraine. The following trends in the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Pang et al (2014) used an empirical method to prove that investment in the IT system could save the government expenditures. Novachenko et al (2020) identified five trends of applying IT in the background of digital transformation in public administration; they believed digital transformation could win more institutional support in public administration and ensure public control over the activity of executive bodies by increasing the accountability and transparency of civil services. Yang et al (2020) found that information communication technology (ICT) enabled governments to act quickly and efficiently in releasing information to the public in crisis and emergencies.…”
Section: Modern Information Technology Used In Government Administrationmentioning
confidence: 99%
“…Pang et al (2014) used an empirical method to prove that investment in the IT system could save the government expenditures. Novachenko et al (2020) identified five trends of applying IT in the background of digital transformation in public administration; they believed digital transformation could win more institutional support in public administration and ensure public control over the activity of executive bodies by increasing the accountability and transparency of civil services. Yang et al (2020) found that information communication technology (ICT) enabled governments to act quickly and efficiently in releasing information to the public in crisis and emergencies.…”
Section: Modern Information Technology Used In Government Administrationmentioning
confidence: 99%